Prey selection of the Red King Crab (Paralithodes camtschaticus) preying on lumpfish eggs (Cyclopterus lumpus), sea urchins (Strongylocentrotus droebachiensis) and scallops (Chlamys islandica) - Michelsen, Helena Kling (Universitetet i Tromsø, 2011)
The red king crab, Paralithodes camtchaticus, is a new generalist predator in the Barents Sea and may have negative effects upon the commercially fished lumpfish eggs (Cyclopterus lumpus), sea urchins (Strongylocentrotus droebachiensis) and scallops (Chlamys islandica). Generalist predators consume an array of prey types, but have been shown to select certain prey over others. To obtain knowledge on how the king crab consume, select and actively select these prey, a laboratory experiment was performed. To detect active selection, the experiment was divided in two parts: first the crabs were given one prey item (no selection) and second they were given all three prey items (selection). Prey organisms consumed was evaluated after 22 hours. There was a significant selection for eggs and scallops and a significant active selection for scallops. The consumption, selection and active selection of prey appeared to be dependent on crab size and availability of alternative prey. With increasing crab size the amount of prey consumed increased and diet composition included a wider array of prey types. Due to the juvenile crabs residence in shallow waters for 5 years until maturation and the adult crabs annual migration to these areas during moulting/spawning, the red king crab predation could have a negative effect on all three prey types.